Study of Effect of Altered Piezometric Heads in Experimental Investigation of Bernoulli’s Equation - Wazeer, Adil; Dubey, Kaushalendra Kumar (Asian Journal of Engineering and Applied Technology, 2019)
Bernoulli’s equation is found to be one of the most popular topics of the elementary physics. The paper presents the experimental behavior of the famous Bernoulli’s equation when the piezometric heads are altered and varied with respect to the heads 10cm and 15cm. The value of h in centimeters have been recorded in altered time periods and heads and in all the nine tubes. The calculation of the total energy (E) by changing the heads is obtained and the results achieved while equating the graphs between the total energy and distance from the reference point by changing the heads has been computed.